3rd AIAA Flow Control Conference 2006
DOI: 10.2514/6.2006-3686
|View full text |Cite
|
Sign up to set email alerts
|

Steady and Unsteady Plasma Wall Jets for Separation and Circulation Control

Abstract: An experimental investigation of separation and circulation control was carried out using corona discharge as well as dielectric barrier discharge actuators at typical micro air vehicle (MAV) Reynolds numbers. All actuators were calibrated by direct measurement and their limitations were assessed on the basis of conventional low Reynolds number active flow control data. Aerodynamic data from corona discharge and high frequency dielectric barrier discharge actuators highlighted their applicability at MAV-type R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(41 citation statements)
references
References 11 publications
5
35
1
Order By: Relevance
“…18a). This agrees with the background literature that clearly supports a sufficient effectiveness of DBD actuation to increase the lift of NACA profile in post-stall regime at the present Reynolds number [1][2][3][4][5][6][7][8]. The change in flow state also induces modifications of the turbulent velocities in the wake region.…”
Section: Time-averaged Velocity F Ieldssupporting
confidence: 89%
See 1 more Smart Citation
“…18a). This agrees with the background literature that clearly supports a sufficient effectiveness of DBD actuation to increase the lift of NACA profile in post-stall regime at the present Reynolds number [1][2][3][4][5][6][7][8]. The change in flow state also induces modifications of the turbulent velocities in the wake region.…”
Section: Time-averaged Velocity F Ieldssupporting
confidence: 89%
“…Previous experimental studies about flow separation controlled by nonthermal plasma actuation have demonstrated that the stall regime can be delayed for NACA 0012 [3], NACA 0015 [4][5][6] or other airfoils profiles [7,8] (Reynolds number up to 4 × 10 5 ). Plasma actuators are attractive for aerospace and MAVs applications because they are simple, lightweight and constitute low-cost devices.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, it has been clarified that the use of unsteady actuation gives a better of capability to the separation control compared with steady actuation [29,31,32]. The unsteady actuation is called the "burst mode" in this study, and the steady actuation is called the "normal mode."…”
mentioning
confidence: 96%
“…The first applications involved external flows, such as around aircraft wings [1,2] operating at atmospheric temperatures and at or below atmospheric pressures. Baughn et al [3] and Porter et al [4] measured SDBD actuators' forces at atmospheric conditions.…”
mentioning
confidence: 99%